Improved Performance of KKG Gugus 4 Patrang Jember Teacher through Development of Materials with Microsoft Publisher - Titin Kartini; Ridho Alfarisi (Pancaran Pendidikan, 2018)
Improving teacher performance as one of the pedagogic competence of teachers so as to generate the expected teachers in Law No. 14 on Teachers and Lecturers. One of the improvements in teacher performance in the learning process is to develop teaching materials in accordance with the environment and characteristics of learners. Two activities are training and mentoring of KKG Gugus 4 Patrang Jember in developing teaching materials with Microsoft Publisher. By using Microsoft Publisher, making a product related to publishing will be easier. In the world of education, LKPD as one of the teaching materials given to the learner to understand a material. Training Activities are given materials about teaching materials and about Microsoft publisher while assistance activities conducted to assist the preparation of teaching materials in accordance with the surrounding environment and characteristics of learners.